Comparison of Lipid Profile in Patients with Chronic Periodontitis and Patients with Healthy Periodontium - Pradhan, Shaili; Shrestha, Rejina; Shrestha Gorkhali, Ranjita; Koirala, Pramod Kumar; Adhikari, Suchana (Journal of Nepalese Society of Periodontology and Oral Implantology, 2022)
Introduction: A positive relationship has been established between periodontal infections and cardiovascular diseases. Among various aetiological factors of cardiovascular diseases, hyperlipidaemia is a major cause. This study aims to compare the lipid profile in patients with chronic periodontitis and healthy periodontium. Objective: The objective of the study was to compare the lipid profile in patients with periodontitis and healthy periodontium. Methods: This analytical cross-sectional study was conducted from August 2020 to January 2021 among a total of 54 subjects recruited in the study who were divided into two groups: chronic periodontitis (CP) group (27 patients) and periodontally healthy group: 27 systemically healthy subjects with healthy periodontium. The periodontal parameters recorded were Plaque index (PI), Gingival index, Probing pocket depth, and Clinical attachment level. Serum levels of lipid profile were measured by enzymatic colorimetric method. Results: The results showed that mean values of triglyceride and very low-density lipoprotein were higher in CP group than periodontally healthy group with significant difference. The mean value of high-density lipoprotein and low-density lipoprotein was lower in CP group than periodontally healthy group and the mean value of total cholesterol was higher in CP group than in periodontally healthy group with no significant difference. Conclusions: Increased serum triglycerides was associated with chronic periodontitis. Chronic periodontitis may cause an increased risk for cardiovascular disease.